Isolation, Identification and Characterization of Amylase Producing Bacteria from Commercial Corn Starch - Elizabeth, K.M.; Maheshwara Rao Kudupa, Ch. V. (Asian Journal of Chemistry, 2010)
Three different bacteria which have the ability to produce amylase enzyme have been isolated from commercial corn starch. They were identified as Bacillus species by performing several biochemical tests and named as Bacillus species I, II and III. The amylase production from these bacteria was assessed at various pH and temperatures. The effect of different substrates on amylase production and the effect of different temperatures on enzyme activity was studied.